Multilayer nickel-coated cobalt-copper-zinc hollow 3D nanospheres and manufacturing method for electrode materials used in hybrid supercapacitors

KR103017658B1Active Publication Date: 2026-09-11UNIVERSITY INDUSTRY COOPERATION GROUP OF KYUNG HEE UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020250008496
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2026-09-11
Estimated Expiration
2045-01-21

Smart Images

  • Figure 112025007892670-PAT00001_ABST
    Figure 112025007892670-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a three-dimensional nanostructure having a multilayer core-shell structure and a method for manufacturing the same, as an electrode material used in high-performance energy storage devices including hybrid supercapacitors. In particular, the invention relates to a technology that maximizes electrochemical performance by forming a multilayer structure having a hollow interior and composed of a nanoparticle layer, a nanocube intermediate layer, and a nanosheet outer layer. Furthermore, the present invention can form a nanostructure having a multilayer structure in which a nanoparticle layer composed of a mixed metal oxide of cobalt, copper, and zinc is used as the inner layer, a nanocube structure composed of cobalt and copper oxides is used as the intermediate layer, and a nanosheet structure composed of nickel oxide or a nickel-cobalt alloy is used as the outer layer. The present invention can be applied to various high-performance energy storage devices, such as hybrid supercapacitors, lithium-ion batteries, and catalytic applications, by achieving simplification of the manufacturing process and cost reduction while providing high energy density and a long lifespan.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a multilayer nickel-coated cobalt-copper-zinc hollow three-dimensional nanosphere used as an electrode material for a hybrid supercapacitor and a method for manufacturing the same. More specifically, it relates to a technology that maximizes electrochemical performance and improves efficiency in energy storage devices through a hollow structure based on a mixed metal oxide of cobalt, copper, and zinc and a multilayer nickel coating. Background Technology

[0002] Over the past few decades, supercapacitors (SC) have garnered attention as an attractive option for rechargeable energy storage systems due to their high power density, extended durability, and fast charging / discharging capabilities.

[0003] Various approaches have been adopted to create highly efficient and effective energy storage electrode materials, including the architectural design of nanomaterials. The architectural design of nanomaterials refers to the morphological definition of nanoparticles present in electrode materials. The shape, size, classification, and dimensions of nanoparticles can influence reaction mechanisms, electrochemical efficiency, and redox activity. To date, various morphological classifications have been reported, each possessing unique advantages corresponding to its respective material. For example, structures such as nanorods, nanowires, nanopools, nanohairs, and nanopillars possess one-dimensional (1D) forms that exhibit reduced diffusion resistance, increased ionic conductivity, and rapid charge transport. Meanwhile, two-dimensional (2D) structures, such as nanosheets and nanoflakes, provide a high surface area that enhances the interaction region between the electrode and the electrolyte. Due to these useful features, two-dimensional (2D) materials are often preferred to achieve high redox performance. Furthermore, 3D nanostructures can exhibit a large number of electroactive sites along with a high surface area for the electrolyte and the material. These structures are known for their enhanced functionality and important roles in redox mechanisms. 3D nanoparticles can be fabricated into various forms depending on surfactants and structure-directing agents. Furthermore, hollow forms have been introduced in energy storage-based research to enhance properties and integrate additional functionalities. This design enables a hollow interior for nanoparticles, providing more space for redox activities. Due to this feature, hollow core-shell nanostructures have been developed that combine the advantages of both architectural structures. The hollow interior acts as an individual reservoir, allowing electrolytes to penetrate deeper layers of the material. This mechanism can induce material wettability, thereby further increasing hydrophilicity. Additionally, the pores of the hollow core provide additional space to accommodate charges and ions, which can positively influence the charging and discharging of the SC. These benefits can be further enhanced if multilayer core-shell type materials can be designed with hollow cores.Designing a core-shell structure with an internal hollow interior, rather than a solid or hollow form, can provide additional active sites that increase the number of redox reactions. Prior art literature

[0004] Korean Registered Patent No. 10-2589325 "Manganese-doped zinc sulfide nanostructures with heat-controlled shape and their application to supercapacitor electrodes" Korean Registered Patent No. 10-1694802 "Method for manufacturing nitrogen-doped multinanochannel porous carbon nanostructures and their application to supercapacitors" Korean Published Patent No. 10-2021-0051276 "Three-dimensional carbon nanostructures and their manufacturing method" The problem to be solved

[0005] The present invention aims to improve the low electrochemical activity and charge / discharge stability of existing energy storage devices.

[0006] The present invention aims to maximize the interaction area between the electrode and the electrolyte by utilizing a hollow structure.

[0007] The present invention aims to improve electrochemical performance and provide high energy density and power density through a multilayer core-shell structure.

[0008] The present invention aims to economically manufacture high-performance electrode materials through low-temperature wet chemical synthesis and simple solvothermal synthesis.

[0009] The present invention aims to develop an electrode material that maintains high stability during more than 20,000 charge-discharge cycles. means of solving the problem

[0010] A three-dimensional nanostructure according to one embodiment has a hollow structure inside, and the hollow structure may include an inner layer formed of a nanoparticle layer composed of cobalt, copper, and zinc, an intermediate layer composed of a nanocube formed on the inner layer, and an outer layer composed of a nanosheet formed on the intermediate layer.

[0011] A method for manufacturing a three-dimensional nanostructure having a hollow core in a multilayer structure according to one embodiment may include the steps of: mixing cobalt acetate, copper acetate, and zinc acetate in an ethylene glycol solvent to form a uniform mixture through ultrasonic treatment and stirring; converting the formed mixture into a nanosphere having a hollow core single shell structure through a solvothermal reaction; immersing the hollow core single shell nanosphere in a solution containing nickel nitrate to form a double shell including a nanosheet structure; and washing and drying the formed nanosphere to manufacture a three-dimensional nanostructure having a multilayer structure. Effects of the invention

[0012] According to one embodiment, the present invention can increase the area capacity of the electrode material to 124.46 μAh cm². According to one embodiment, the present invention can maintain cycle stability of 84% or more during 20,000 charge-discharge cycles.

[0013] The Japanese invention can achieve an energy density of up to 118.9 μWh cm² and a power density of 7,500 μWh cm².

[0014] According to one embodiment, high real-time application suitability can be demonstrated in a lead supercapacitor device.

[0015] According to one embodiment, the present invention can be applied to various electrode materials to increase the possibility of commercialization. Brief explanation of the drawing

[0016] FIG. 1 is a drawing illustrating a three-dimensional nanostructure according to one embodiment. Figure 2 is a diagram illustrating the manufacturing process of CCZ-8 HCSSNSs and Ni@CCZ-8 HCDSNSs. Figure 3 is a diagram disclosing the structural characteristics of Ni@CCZ-8 HCDSNSs, including FESEM, EDS, and TEM images of CCZ-8 and Ni@CCZ-8 materials. Figure 4 is a diagram disclosing the chemical properties of CCZ-8 and Ni@CCZ-8 materials through XRD patterns and XPS analysis results. Figure 5 is a diagram comparing and evaluating the electrochemical characteristics of CCZ-8 / NF and Ni@CCZ-8 / NF electrodes. FIG. 6 is a diagram disclosing the design, performance optimization, and cycling test results of a pouch-type HSC device. FIG. 7 is a drawing disclosing examples of driving an RC car, LED goggles, a DC motor, and a digital clock using an HSC device. Figure 8 is a diagram disclosing the structural characteristics of CCZ-4 and CCZ-12 materials through FESEM images. Figure 9 is a diagram comparing the electrochemical characteristics of CCZ-4 / NF, CCZ-8 / NF, and CCZ-12 / NF electrodes. FIG. 10 is a diagram disclosing the CV, GCD curves, and area capacitance characteristics of the CCZ-4 / NF electrode. FIG. 11 is a diagram disclosing the CV, GCD curves, and area capacitance characteristics of the CCZ-8 / NF electrode. FIG. 12 is a diagram disclosing the CV, GCD curves, and area capacitance characteristics of the CCZ-12 / NF electrode. FIG. 13 is a diagram disclosing the CV, GCD curves, and area capacitance characteristics of an AC / NF electrode. FIG. 14 is a drawing illustrating a method for manufacturing a three-dimensional nanostructure according to one embodiment. Specific details for implementing the invention

[0017] Specific structural or functional descriptions of embodiments according to the concept of the present invention disclosed herein are provided merely for the purpose of explaining embodiments according to the concept of the present invention, and embodiments according to the concept of the present invention may be implemented in various forms and are not limited to the embodiments described herein.

[0018] Embodiments according to the concept of the present invention may be subject to various modifications and may take various forms; therefore, embodiments are illustrated in the drawings and described in detail in this specification. However, this is not intended to limit the embodiments according to the concept of the present invention to specific disclosed forms, and includes modifications, equivalents, or substitutions that fall within the spirit and scope of the present invention.

[0019] Terms such as "first" or "second" may be used to describe various components, but said components should not be limited by said terms. For the sole purpose of distinguishing one component from another, for example, without departing from the scope of rights according to the concept of the present invention, the first component may be named the second component, and similarly, the second component may be named the first component.

[0020] When it is stated that one component is "connected" or "connected" to another component, it should be understood that while it may be directly connected or connected to that other component, there may also be other components in between. Conversely, when it is stated that one component is "directly connected" or "directly connected" to another component, it should be understood that there are no other components in between. Expressions describing the relationships between components, such as "between," "exactly between," or "directly adjacent to," should be interpreted in the same way.

[0021] The terms used herein are used merely to describe specific embodiments and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise. In this specification, terms such as “comprising” or “having” are intended to specify the existence of the described features, numbers, steps, actions, components, parts, or combinations thereof, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.

[0022] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this specification.

[0024] Hereinafter, embodiments will be described in detail with reference to the attached drawings. However, the scope of the patent application is not limited or restricted by these embodiments. Identical reference numerals in each drawing indicate identical components.

[0026] FIG. 1 is a diagram showing the structure of a three-dimensional nanostructure (100) according to the present invention. This nanostructure includes a multilayer core-shell structure composed of an inner layer (110), an intermediate layer (120), and an outer layer (130), and each layer is designed to perform a unique functional role.

[0027] The inner layer (110) consists of a nanoparticle layer having a hollow structure.

[0028] The hollow structure of the inner layer (110) has an average diameter of the internal space within the range of 500 to 1000 nm and is designed so that the electrolyte can penetrate deeply into the structure.

[0029] The nanoparticle layer of the inner layer (110) is composed of a mixed metal oxide consisting of cobalt (Co), copper (Cu), and zinc (Zn), and this combination of materials increases the density of electrochemically active sites to maximize reactivity.

[0030] The nanoparticles of the inner layer (110) have an average particle size within the range of 1050 nm and provide a high surface area, which is advantageous for redox reactions. The inner layer is a layer that forms the basis of a multilayer core-shell structure, increasing interaction with the electrolyte and maximizing electrochemical reactivity.

[0031] The intermediate layer (120) consists of nanocubes formed on the inner layer (110). The nanocubes of the intermediate layer (120) have an average side length in the range of 50 to 200 nm and are composed of cobalt (Co) and copper (Cu) oxides.

[0032] The intermediate layer (120) is arranged in a nanocube structure to provide a high surface area, which additionally provides electrochemically active sites to enhance redox reactions.

[0033] The intermediate layer (120) provides a structural connection between the inner layer and the outer layer and serves to maintain the mechanical stability of the entire structure. The nanocube arrangement of the intermediate layer increases accessibility to electrochemical active sites and enhances ion conductivity, thereby improving electrochemical performance.

[0034] The outer layer (130) consists of nanosheets formed on the intermediate layer (120). The nanosheets of the outer layer (130) are mainly composed of nickel (Ni) oxide or nickel-cobalt alloy and are designed to serve as electrode materials.

[0035] The nanosheets of the outer layer (130) have a thickness in the range of 5 to 20 nm and provide electrochemical activation and structural stability simultaneously.

[0036] The surface of the outer layer (130) is finished with a nickel coating within a thickness range of 1050 nm, and this coating is formed through a chemical vapor deposition process.

[0037] The outer layer (130) has a two-dimensional structure and provides a high surface area, which maximizes electrochemical active sites and improves the electrochemical performance of the hybrid supercapacitor. The outer layer increases the charge / discharge stability of the supercapacitor and strengthens the durability of the electrode through a nickel coating.

[0038] The three-dimensional nanostructure (100) includes a multilayer core-shell structure composed of an inner layer (110), an intermediate layer (120), and an outer layer (130), and each layer is interconnected to maximize electrochemical performance.

[0039] The multilayer core-shell structure provides an internal empty space including a hollow structure, which allows the electrolyte to penetrate to deep layers of the material.

[0040] The hollow structure has a porosity set within the range of approximately 30–70%, which increases the density of electrochemically active sites and enhances the efficiency of redox reactions. Each layer is bonded by chemical interactions to maintain the stability of the overall structure and simultaneously ensure mechanical and electrical performance.

[0041] Three-dimensional nanostructures provide high energy density and excellent charge / discharge performance through a combination of multilayer core-shell structures and hollow structures.

[0042] Three-dimensional nanostructures are used as electrode materials for hybrid supercapacitors and provide high power density and energy density simultaneously.

[0043] The structure of the present invention can be utilized in various application fields, such as energy storage devices, batteries, and electrochemical reaction systems. The present invention provides superior morphological stability and electrochemical reactivity compared to existing energy storage materials, and has high potential for commercialization. The structure of the present invention can provide long-term energy storage solutions through high cycle stability and a long lifespan.

[0044] FIG. 2 is a drawing (200) disclosing a process for manufacturing a three-dimensional nanostructure according to one embodiment based on CCZ-8 HCSSNSs and Ni@CCZ-8 HCDSNSs.

[0045] A three-dimensional nanostructure according to one embodiment has a hollow internal structure and is characterized by a multilayer core-shell structure composed of a nanoparticle internal layer, a nanocube intermediate layer, and a nanosheet external layer. The hollow structure has an average internal diameter within the range of 500 to 1000 nm and is formed through a solvothermal synthesis process using ethylene glycol as a solvent. In the solvothermal synthesis process, polyvinylpyrrolidone (PVP) is used as a structural indicator, which helps with the uniform dispersion and stabilization of metal ions.

[0046] The nanoparticle layer is formed from a mixed metal oxide composed of cobalt, copper, and zinc, with an average particle size of 10 to 50 nm. This layer covers the interior of the hollow structure, and a nanocube-shaped intermediate layer is formed on top of it. The intermediate layer consists of a nanocube structure arranged with cobalt and copper oxides, with an average side length in the range of 50 to 200 nm. On top of this intermediate layer, a nanosheet outer layer finished with a nickel coating is formed. The outer layer has a thickness in the range of 10 to 50 nm and is composed of nickel oxide or a nickel-cobalt alloy. This outer layer is formed by a chemical vapor deposition process or by immersing the hollow structure in a nickel nitrate solution and heating it.

[0047] Each layer is stably connected by chemical interactions and assembled into a multilayer core-shell structure. This structure has a porosity within the range of 30–70%, maximizing the contact area with the electrolyte and increasing the density of electrochemically active sites. This design is suitable for use as an electrode material for hybrid supercapacitors and provides high energy density and excellent cycle stability.

[0048] The 3D nanostructure is assembled to have a multilayer structure after drying treatment, ensuring high mechanical stability and electrochemical performance through chemical interactions between the inner, middle, and outer layers. In particular, the nickel coating on the outer layer enhances electrical conductivity, and the thin structure in the form of nanosheets improves reaction rates, thereby maximizing electrochemical properties.

[0049] This structure can be applied to various energy storage and conversion devices and is specifically designed for performance optimization of hybrid supercapacitors. This allows for increased electrochemical reaction efficiency and simultaneously ensures the lifespan and stability of the electrodes.

[0050] More specifically, FIG. 2 is a diagram detailing the manufacturing process of multilayer three-dimensional nanostructures (CCZ-8 HCSSNSs and Ni@CCZ-8 HCDSNSs) having a hollow internal structure and comprising a nanoparticle layer, a nanocube intermediate layer, and a nanosheet outer layer. Each manufacturing step is described in detail as follows.

[0052] Manufacturing process of CCZ-8 HCSSNSs

[0053] 1. Mixture formation step

[0054] Addition of mixture components: Cobalt acetate (Co(CH3CO2)2·4H2O, 50 mM), copper acetate (Cu(CH3CO2)2·H2O, 20 mM), and zinc acetate (Zn(CH3CO2)2·2H2O, 30 mM) are added sequentially to ethylene glycol (100 ml).

[0055] Addition of structural indicator: Polyvinylpyrrolidone (PVP) is added as a structural indicator to maintain the uniform dispersion and stability of metal ions in solution. PVP prevents ion aggregation by forming hydrogen bonds with metal ions.

[0056] Homogenization of the solution: The added mixture is prepared to become a homogeneous mixture through ultrasonic treatment and strong stirring. Ultrasonic treatment helps in the complete dissolution of metal ions.

[0058] 2. Solventothermal reaction step

[0059] Heat treatment conditions: The mixture is placed in an autoclave and heat-treated at 160°C for 8 hours. During this process, the high temperature and pressure inside the autoclave induce a core-shell arrangement of metal ions.

[0060] Inner layer formation process: Metal ions aggregate into an inner layer under the structural directing effect of PVP and the polar environment of ethylene glycol to form a nanoparticle layer. This layer consists of mixed metal oxides of cobalt, copper, and zinc, with an average particle size of 10–50 nm.

[0061] Intermediate layer formation process: An intermediate layer in the form of nanocubes is additionally formed on top of the inner layer. The intermediate layer is composed of cobalt and copper oxides, and has an average side length of 50 to 200 nm.

[0063] 3. Washing and drying steps

[0064] Separation of precipitate: Hollow core single-shell nanospheres (CCZ-8 HCSSNSs) produced after solvothermal reaction are separated into precipitates using a centrifuge.

[0065] Removal of impurities: The precipitate is repeatedly washed with deionized water (DIW) and ethanol to completely remove residual reaction byproducts.

[0066] Drying and structural stabilization: The washed precipitate is dried at 70°C for 24 hours, and finally, CCZ-8 HCSSNSs having a hollow internal structure are formed.

[0068] Manufacturing process of Ni@CCZ-8 HCDSNSs

[0069] 1. Preparation step of the nickel coating mixture

[0070] Preparation of mixture: Nickel nitrate (Ni(NO3)2·6H2O, 5 mM) is completely dissolved in deionized water (50 ml). At this time, nickel ions (Ni²) and nitrate ions (NO3) are uniformly dispersed in the solution.

[0071] Addition of CCZ-8 HCSSNSs: CCZ-8 HCSSNSs (0.3 g) are added to the prepared nickel solution, and nickel ions are uniformly adsorbed onto the surface of nanospheres through strong stirring and ultrasonic treatment.

[0073] 2. Heating and nickel coating formation step

[0074] Heating conditions: The mixture is heated at 90°C for 2 hours.

[0075] External layer formation process: During the heating process, nickel ions (Ni²⁺) are adsorbed onto the surface of CCZ-8 HCSSNSs to form an external layer in the form of nanosheets.

[0076] Nickel coating completion: The thickness of the outer layer is maintained at approximately 10–50 nm, and hollow core double-shell nanospheres (Ni@CCZ-8 HCDSNSs) are completed.

[0078] 3. Washing and drying steps

[0079] Washing process: The Ni@CCZ-8 HCDSNSs generated after heating are separated into a precipitate using a centrifuge, and the remaining reaction byproducts are removed by washing with deionized water and ethanol.

[0080] Drying and structural stabilization: The washed precipitate is dried at 70°C for 24 hours to form stabilized Ni@CCZ-8 HCDSNSs.

[0081] Ni@CCZ-8 HCDSNSs have a multilayer structure consisting of an inner layer, an intermediate layer, and an outer layer. The inner layer is a nanoparticle layer composed of mixed metal oxides of cobalt, copper, and zinc, with an average particle size of 10–50 nm. The intermediate layer is a nanocube layer arranged with cobalt and copper oxides, with an average side length of 50–200 nm. The outer layer is a nanosheet layer composed of nickel oxide or a nickel-cobalt alloy, with a thickness of 5–20 nm.

[0082] This structure includes a hollow structure, and the internal space of the hollow structure is formed with an average diameter of 500–1000 nm, designed to allow the electrolyte to easily penetrate into the structure. The porosity is maintained at 30–70%, contributing to an increase in the density of electrochemically active sites. The multilayer structure, consisting of an inner layer, a middle layer, and an outer layer, provides high electrochemical performance as each layer is stably connected through chemical interactions.

[0083] FIG. 2 describes the manufacturing process of CCZ-8 HCSSNSs and Ni@CCZ-8 HCDSNSs in detail step by step, specifically disclosing their respective structural characteristics and details of the manufacturing process. Each step faithfully reflects the wording and terminology of the claims and clearly demonstrates the technical advantages of the hollow structure and multilayer structure.

[0084] FIG. 3 is a drawing (300) disclosing the structural characteristics of Ni@CCZ-8 HCDSNSs, including FESEM, EDS, and TEM images of CCZ-8 and Ni@CCZ-8 materials.

[0085] FIG. 3 discloses in detail the structural characteristics and physical properties of CCZ-8 and Ni@CCZ-8 materials, including a multilayer structure in which the interior of the three-dimensional nanostructure is designed as a hollow structure and various analysis data supporting it.

[0086] Figure 3 (a)(i) includes low-magnification FESEM images of the CCZ-8 material. These images show that the interior has a hollow structure and that three-dimensional nanostructures composed of a nanoparticle layer, a nanocube intermediate layer, and a nanosheet outer layer are arranged in a cluster form.

[0087] Each nanosphere is formed as an independent unit, and the characteristic of having a hollow structure inside is emphasized. Figures 3(a) and 3(ii) include high-magnification FESEM images. These images show that the inner layer of the nanostructures of the CCZ-8 material consists of a layer of nanoparticles composed of cobalt, copper, and zinc.

[0088] An intermediate layer composed of nanocubes is formed on top of this inner layer, and this hollow structure can be visually confirmed to have an internal diameter within the range of approximately 500 to 1000 nm.

[0089] The internal structure is consistent with the design features of the hollow structure mentioned in the claim. FIG. 3 (b)(i) includes a low-magnification FESEM image of the Ni@CCZ-8 material, showing a 3D nanosphere designed with a multilayer core-shell structure coated as an outer layer of nanosheets.

[0090] This structure is characterized by an outer layer finished with a nickel coating, suggesting that the thickness of the outer layer is within the range of approximately 1050 nm. This is consistent with the nickel coating thickness characteristics. Figure (b)(ii) includes a high-magnification FESEM image and more clearly shows the structure in which the surface of the nanosphere is covered with nickel nanosheets. This outer layer consists of porous nanosheets and is formed on the middle and inner layers of the nanosphere.

[0091] Figure 3(c) contains the EDS spectrum for the Ni@CCZ-8 material. The EDS spectrum confirms that the elements Ni (nickel), Co (cobalt), Cu (copper), Zn (zinc), C (carbon), O (oxygen), and N (nitrogen) are evenly distributed in each layer of the nanostructure. The nickel (Ni) element is mainly detected in the outer layer, which is consistent with the characteristic that the outer layer is finished with a nickel coating.

[0092] Cobalt (Co), copper (Cu), and zinc (Zn) elements are primarily detected in the inner and intermediate layers. This result demonstrates that mixed metal oxides of cobalt, copper, and zinc are the major components of the inner and intermediate layers.

[0093] Figure 3 (d)(i-viii) includes elemental mapping images generated via EDS, visually demonstrating that each element is uniformly distributed within the nanostructure. Nickel (Ni) is evenly distributed in the outer layer. Cobalt (Co) is detected in the inner and middle layers. Copper (Cu) is observed in the middle and inner layers. Zinc (Zn) is predominantly found in the inner layer. Oxygen (O) is widely distributed throughout the nanostructure, indicating that each layer is composed of metal oxides. Figure (e)(i) includes low-magnification TEM images of the Ni@CCZ-8 material, showing that nanospheres with a multilayer core-shell structure designed with a hollow interior are arranged in a cluster form. Each nanosphere has a hollow core, which is designed to facilitate electrolyte penetration. High-magnification TEM images clearly show a multilayer structure of nanospheres composed of an inner layer (nanoparticle layer), an intermediate layer (nanocube layer), and an outer layer (nanosheet layer). The thickness and shape of each layer reflect the nanosheet thickness and the average side length characteristics of the intermediate layer.

[0094] Figure 3 (e)(iii) shows that the outer layer of the nanosheet has a porous structure and completely covers the surface of the nanosphere. The selected region electron diffraction (SAED) pattern indicates that the material has amorphous properties, which is consistent with the chemical interaction characteristics of the core-shell structure.

[0095] FIG. 4 is a diagram (400) disclosing chemical properties through XRD patterns and XPS analysis results of CCZ-8 and Ni@CCZ-8 materials.

[0096] In particular, Figure 4 includes X-ray diffraction (XRD) patterns and X-ray photoelectron spectroscopy (XPS) analysis results. Figure (a) shows the XRD patterns of CCZ-8 and Ni@CCZ-8 materials. In the XRD analysis results, neither CCZ-8 nor Ni@CCZ-8 materials show distinct high-intensity peaks, which clearly demonstrates that both materials have amorphous characteristics. These amorphous characteristics are also observed in the selected region electron diffraction (SAED) pattern results and are confirmed as structural features lacking intrinsic grain boundaries.

[0097] Figure 4(b) includes the full XPS spectrum for the Ni@CCZ-8 material and shows the binding energies of major elements such as Zn 2p, Cu 2p, Ni 2p, Co 2p, O 1s, N 1s, and C 1s. In the full XPS spectrum, each element forms a distinct peak in the corresponding binding energy range, clearly demonstrating the chemical composition of the Ni@CCZ-8 material.

[0098] Figure 4(c)(i) shows the high-resolution XPS spectrum of Zn 2p. In the spectrum, the Zn 2p3 / 2 peak is observed at 1020.41 eV and the Zn 2p1 / 2 peak is observed at 1043.49 eV, indicating the presence of the Zn2+ oxidation state. These peaks demonstrate that Zn acts as a component of the intermediate and inner layers.

[0099] Figure 4(c)(ii) includes high-resolution XPS spectra of Cu 2p, and Cu 2p 3 / 2 The peak is at 933.15 eV, Cu 2p 1 / 2 A peak is observed at 953.28 eV. These peaks represent Cu / Cu+ and Cu2+ oxidation states, indicating the presence of copper in the intermediate layer. Additionally, satellite peaks appear at 941.08 eV and 961.17 eV, suggesting that copper exists in multiple oxidation states.

[0100] Figure (c)(iii) shows the high-resolution XPS spectrum of Ni 2p. Ni 2p 3 / 2 The peak is at 854.57 eV, Ni 2p 1 / 2 A peak is observed at 872.20 eV, which clearly demonstrates the presence of Ni2+ and Ni3+ oxidation states. Satellite peaks appear at 860.82 eV and 878.76 eV, indicating that nickel acts as a major component of the outer layer.

[0101] Figure (c)(iv) includes the high-resolution XPS spectrum of Co 2p, and Co 2p 3 / 2 The peak is at 779.86 eV, Co 2p 1 / 2 A peak appears at 795.55 eV. This peak indicates that cobalt exists in CO2+ and CO3+ oxidation states, suggesting that it acts as a major component of the inner and intermediate layers. Satellite peaks are identified at 785.87 eV and 802.11 eV.

[0102] Figures (c) and (v) contain the high-resolution XPS spectrum of O 1s, showing four major peaks. The peak (O1) observed at 529.51 eV represents metal-oxygen bonding (MO), and the peak (O2) appearing at 530.04 eV represents oxygen defects and low oxygen coordination. The peak (O3) at 530.74 eV represents chemically or physically adsorbed water molecules, and the peak (O4) appearing at 531.48 eV represents oxygen-carbon bonding (O=C). This oxygen bonding information confirms the metal oxide characteristics of the Ni@CCZ-8 material.

[0103] Figure (c)(vi) contains the high-resolution XPS spectrum of N 1s, where the peak at 398.91 eV (N1) represents pyrrolic nitrogen and the peak at 400.6 eV (N2) represents graphitic nitrogen. The peak at 402.11 eV (N3) represents a nitrogen-oxygen bond (NO). This nitrogen bonding state contributes to the chemical composition and electrochemical properties of the material.

[0104] Figure (c)(vii) shows the high-resolution XPS spectrum of C 1s. The peak at 283.59 eV (C1) represents a CC bond resulting from the sp2 hybridization of carbon atoms, and the peak at 284.72 eV (C2) represents a C=C bond. The peak at 287.36 eV (C3) represents CO and C=O bonds. This carbon bonding information plays an important role in the structural stability and electrochemical performance of Ni@CCZ-8.

[0105] The above analysis results clearly identify the chemical composition and oxidation state of the Ni@CCZ-8 material and support that the multilayer hollow structure of the present invention provides excellent electrochemical properties for energy storage applications. These details are in perfect agreement with the characteristics of the nickel-coated cobalt copper zinc nanospheres described in the claims.

[0106] FIG. 5 is a diagram (500) comparing and evaluating the electrochemical characteristics of CCZ-8 / NF and Ni@CCZ-8 / NF electrodes.

[0107] In particular, Figure 5 compares and evaluates the electrochemical characteristics of CCZ-8 / NF and Ni@CCZ-8 / NF electrodes, and specifically explains the electrochemical reactivity, capacity retention rate, charge-discharge performance, and the contribution of the electrode structure. The details of each part of Figure 5 are described in detail below.

[0108] Figure (a) shows the cyclic voltammetry (CV) curves of the CCZ-8 / NF and Ni@CCZ-8 / NF electrodes. These CV measurements were performed at a scan rate of 15 mV / s. The Ni@CCZ-8 / NF electrode exhibits a higher current response compared to the CCZ-8 / NF electrode, which indicates that the nanostructure of the Ni@CCZ-8 / NF electrode provides more electrochemically active sites. Additionally, the redox peaks observed in the Ni@CCZ-8 / NF electrode are more distinct compared to the CCZ-8 / NF electrode, suggesting that the nickel coating layer plays an important role in the redox reaction.

[0109] Figure (b) shows the charge-discharge (GCD) curves of the CCZ-8 / NF and Ni@CCZ-8 / NF electrodes. These measurements were performed at a current density of 3 mA / cm². The Ni@CCZ-8 / NF electrode exhibits a longer discharge time compared to the CCZ-8 / NF electrode, which demonstrates that the Ni@CCZ-8 / NF electrode possesses a higher electrochemical capacity. In particular, the shape of the discharge curve highlights the Faradic reaction characteristics of the Ni@CCZ-8 / NF electrode, indicating increased ion and electron mobility due to the multilayer nanostructure.

[0110] Figure (c) shows the areal capacitance calculated based on GCD data of the CCZ-8 / NF and Ni@CCZ-8 / NF electrodes. At a current density of 3 mA / cm², the CCZ-8 / NF electrode exhibits an areal capacitance of 51.5 μAh / cm², while the Ni@CCZ-8 / NF electrode records an areal capacitance of 123.36 μAh / cm². This indicates that the areal capacitance of the Ni@CCZ-8 / NF electrode is approximately 2.4 times higher, demonstrating that the nanostructure and nickel coating significantly improved electrochemical performance.

[0111] Figure (d) shows the CV curves of the Ni@CCZ-8 / NF electrode at various scan rates (5–30 mV / s). As the scan rate increases, the area under the CV curve gradually increases, indicating that the electrode material possesses rapid electrochemical reactivity. In particular, redox peaks are clearly observed at all scan rates, demonstrating that the Ni@CCZ-8 / NF electrode provides stable performance under various electrochemical conditions.

[0112] Figure (e) shows the GCD curves of the Ni@CCZ-8 / NF electrode at various current densities (2–10 mA / cm²). At low current densities, the discharge time is sustained for a long period, suggesting that ions are effectively diffusing into the nanostructure. As the current density increases, the discharge time decreases, but the discharge curve maintains a non-linear shape, highlighting the contribution of the Faradic reaction.

[0113] Figure (f) shows the change in areal capacitance of the Ni@CCZ-8 / NF electrode with respect to current density. The Ni@CCZ-8 / NF electrode records a maximum areal capacitance of 123.36 μAh / cm² at 2 mA / cm², showing a slight decrease as the current density increases. This demonstrates that the Ni@CCZ-8 / NF electrode maintains excellent electrochemical performance even at high current densities.

[0114] Figure (g) shows the long-term cycle stability of the Ni@CCZ-8 / NF electrode. Even after 20,000 charge-discharge cycles at 7 mA / cm², the Ni@CCZ-8 / NF electrode retains 87.4% of its initial capacity, demonstrating the electrode's excellent durability. The inset FESEM image visually confirms that the surface structure of the Ni@CCZ-8 / NF electrode is well maintained even after cycling. The inset EIS data shows the change in resistance before and after cycling; although a slight increase is observed after cycling, the Ni@CCZ-8 / NF electrode still maintains low charge transfer resistance.

[0115] Figure (h) includes an exploded schematic view illustrating the structural characteristics of the Ni@CCZ-8 / NF electrode. The interior features a hollow structure that facilitates electrolyte penetration and optimizes ion transport pathways. The middle layer consists of nanocubes to increase the surface area, while the outer layer is composed of porous nickel nanosheets to provide high electrochemical reactivity. These structural characteristics contribute to the electrode material exhibiting superior performance in energy storage devices.

[0116] The electrochemical analysis results shown in Figure 5 above indicate that the Ni@CCZ-8 / NF electrode exhibits improved electrochemical performance compared to the CCZ-8 / NF electrode, clearly demonstrating that the multilayer nanostructure and nickel coating are the primary contributing factors. The Ni@CCZ-8 / NF electrode holds great potential in energy storage and hybrid supercapacitor (HSC) applications.

[0117] FIG. 6 is a drawing (600) disclosing the design, performance optimization, and cycling test results of a pouch-type HSC device.

[0118] Specifically, FIG. 6 discloses in detail the design, performance optimization, and electrochemical characteristics of a pouch-type hybrid supercapacitor (HSC) device. The figure includes the structure of the device, results of electrochemical characteristic evaluation, and long-term cycle stability, and specifically describes the performance and applicability of the technology implemented in the present invention.

[0119] Figure (a) of the drawing schematically illustrates the structure of a pouch-type HSC device. The device has an outer case composed of plastic-laminated aluminum, and nickel foam (NF) is used as an electrode inside. A separator is positioned between the two electrodes to allow the electrolyte to pass through while preventing a short circuit between the electrodes. The electrolyte consists of a 2M KOH solution, which provides high ionic conductivity. Nickel terminals are designed to enable electrical connection and maintain electrochemical stability of the entire system.

[0120] Figure (b) shows the cyclic voltammetry (CV) curve of the pouch-type HSC device. This test was performed at a scan rate of 15 mV / s, and the voltage window was extended from 1.0 V to 1.65 V. The CV curve shows a stable redox peak up to 1.55 V, indicating that the device has electrochemical reactivity and can effectively store energy. At voltages exceeding 1.65 V, the CV curve is distorted, confirming that the upper limit of the operating voltage window is 1.55 V.

[0121] Figure (c) shows the charge-discharge (GCD) curve of a pouch-type HSC device measured at a current density of 3 mA / cm². The discharge curve maintains a linear shape up to 1.55 V, indicating stable energy storage and release. However, at voltages above 1.65 V, the discharge curve becomes distorted, highlighting that the voltage window at which the device performs optimally is 1.55 V or lower.

[0122] Figure (d) shows CV curves measured at various scan rates (5–50 mV / s). As the scan rate increases, the area under the CV curve gradually increases, indicating that the device exhibits a fast and stable redox reaction. At all scan rates, the CV curves contain distinct redox peaks, demonstrating that the electrochemically active sites are being fully utilized.

[0123] Figure (e) shows the GCD curves measured at various current densities (1.5–10 mA / cm²). At low current densities, the discharge time is maintained for a long period, suggesting that ion diffusion into the device has occurred effectively. As the current density increases, the discharge time decreases, but the nonlinear nature of the discharge curve is maintained, which highlights the Faradic response characteristics of the device.

[0124] Figure (f) represents the areal capacitance calculated based on GCD data. The pouch-type HSC device records an areal capacitance of up to 385 mF / cm² at 1.5 mA / cm², with the capacitance decreasing slightly as the current density increases. This indicates that the device still maintains excellent electrochemical performance even at high current densities.

[0125] Figure (g) is the Ragone plot of the HSC device, showing the correlation between areal energy density and areal power density. The device records an areal energy density of up to 118.9 μWh / cm² and an areal power density of 7,500 μW / cm². This demonstrates the excellent performance of the pouch-type HSC device, which can simultaneously deliver high energy and high power. The inset image shows an actual photograph of the pouch-type HSC device used in the experiment.

[0126] Figure (h) shows the results of a long-term cycling test of the HSC device. 40,000 charge-discharge cycles were performed at a current density of 7 mA / cm², and the device retained 88.6% of its initial capacity. These results demonstrate that the device possesses excellent durability. During the first 10,000 cycles of the test, the device undergoes an activation phase, and the capacity retention rate increases to 226%. This indicates that the phenomenon is due to the electrochemical activation of the electrode material. The inserted EIS (impedance spectroscopy) data shows the changes in Rs (internal resistance) and Rct (charge transfer resistance) before and after cycling. Although the values ​​of Rs and Rct increased slightly after cycling, this is interpreted as a natural result of the long-term cycling test.

[0127] The results of Fig. 6 clearly demonstrate that a pouch-type HSC device combining a Ni@CCZ-8 / NF electrode and an AC / NF electrode provides excellent electrochemical performance in high-energy and high-power applications. Furthermore, the pouch-type HSC device implemented in the present invention provides long-term stability and durability, demonstrating that it can be usefully utilized in actual energy storage applications.

[0128] FIG. 7 is a drawing (700) disclosing examples of driving an RC car, LED goggles, a DC motor, and a digital clock using an HSC device.

[0129] In particular, FIG. 7 demonstrates the practical applicability and electrochemical performance of the present invention. Figure (a) shows a schematic diagram of a power supply and signal transmission system. The HSC device shows two supercapacitors, named Device-1 and Device-2, connected in series. The series connection of the HSC device increases the output voltage window to meet the driving requirements of a device such as an RC car. The transmitting unit consists of a transmission circuit inside the RC remote control and serves to wirelessly transmit signals. The receiving unit consists of a receiving circuit included inside the RC car, which receives the transmitted signal and converts it into an electrical signal. The received signal is transmitted to DC Motor-1 and DC Motor-2 to provide driving power for the RC car. The state in which the RC remote control and the HSC device are connected can be seen in Figure (b)(i). The RC remote control uses the HSC device as a power source, which indicates that the device is supplying sufficient power. Figure (b)(ii) shows an activated LED Power On indicator, which indicates that the RC remote control is powered on. This demonstrates that the HSC device is stably supplying power to the RC remote control. Figures (b) and (iii) show the RC remote control operating normally and controlling the RC car. The signal transmitted from the RC remote control is delivered to the receiving circuit of the RC car to activate the DC motor, and the movement of the RC car can be observed.

[0130] The operation of the LED goggles is shown in Figure (c). Figure (c)(i) shows the LED goggles and the HSC device separated. In this state, the LED goggles are inactive as no power is supplied. Figure (c)(ii) shows the HSC device and the LED goggles connected; in this state, the LED goggles are activated and emit bright light. The LED goggles operate stably even at low power, indicating that the HSC device is providing sufficient power. Figure (c)(iii) shows the LED goggles turned on in a dark environment. The LED goggles maintain high brightness even in a dark environment, confirming the stable power supply capability of the HSC device.

[0131] The operation of the DC motor is shown in Figure (d). Figure (d)(i) shows the state in which the HSC device and the DC motor are connected. The HSC device supplies power to the DC motor, thereby enabling the motor to operate successfully. Figure (d)(ii) shows the operation state of the DC motor at high magnification. The rotation of the motor demonstrates the ability of the HSC device to handle high current loads, which highlights the high electrochemical performance of the present invention.

[0132] The operation of the digital clock is shown in Figure (e). Figure (e)(i) shows the digital clock connected to an HSC device. The digital clock is powered by the HSC device, which demonstrates the potential for using the HSC device in small electronic devices. Figure (e)(ii) shows the digital clock operating normally and displaying the time. The HSC device reliably supplies power to the digital clock for about 30 minutes on a single charge and provides excellent performance even when operating small electronic devices.

[0133] As shown above, FIG. 7 demonstrates that the HSC device can operate as a reliable power source in various electronic devices, showing its potential as a multi-purpose energy storage device ranging from high-power devices such as RC cars to low-power devices such as LED goggles and digital watches. The HSC device clearly demonstrates the technical advancement and applicability of the present invention.

[0134] FIG. 8 is a drawing (800) disclosing structural characteristics through FESEM images of CCZ-4 and CCZ-12 materials.

[0135] Specifically, FIG. 8 explains the characteristics of each nanostructure in connection with the technical configuration defined in the claims.

[0136] Drawing (a)(i) shows a low-magnification FESEM image of the CCZ-4 material. This image indicates that the CCZ-4 material has a clustered form composed of nanospheres. The nanospheres of CCZ-4 are arranged as independent units, and the average diameter of each nanosphere is measured to be about 3 μm. These size and shape are consistent with the characteristics of nanospheres having a porous hollow structure mentioned in the claims.

[0137] Drawings (a) and (ii) show high-magnification FESEM images of the CCZ-4 material. These images clearly indicate that the nanospheres are designed with a hollow interior structure. The hollow interior of the nanospheres serves to facilitate the movement of ions and electrons for electrochemical reactions. The hollow structure is observed to have an internal diameter of approximately 600 nm, which is consistent with the optimal design conditions for the internal hollow structure described in the claims.

[0138] Drawings (a) and (iii) show higher magnification FESEM images of the CCZ-4 material. These images clearly show that a layer of nanoparticles is uniformly formed on the surface of the nanospheres. The thickness of the nanoparticle layer is measured to be in the range of about 50 to 100 nm, which acts as an important factor in increasing electrochemical reactivity. These surface characteristics are consistent with the design of the porous surface layer of the nanostructure defined in the claims.

[0139] Figure (b)(i) shows a low-magnification FESEM image of the CCZ-12 material. This image shows a nanosphere cluster morphology similar to CCZ-4, but CCZ-12 has a more densely arranged nanosphere structure. The average diameter of the nanospheres in CCZ-12 is maintained at approximately 3 μm, but the surface density is observed to be higher than that of CCZ-4. These features are consistent with the design for increased surface density of nanospheres described in the claims.

[0140] Figure (b)(ii) shows a high-magnification FESEM image of the CCZ-12 material. This image shows that a nanocube layer is formed on the surface of the nanosphere. The nanocube layer is an intermediate layer of a multilayer structure formed between the hollow structure and the outer surface, and is observed to have an average side length of about 200 to 300 nm. The nanocube layer increases the number of electrochemically active sites, which satisfies the technical objective of the intermediate layer design defined in the claim.

[0141] Figures (b) and (iii) show higher-magnification FESEM images of the CCZ-12 material. These images reveal a structure in which nanocube layers are densely arranged on the surface of nanospheres, suggesting that the nanospheres of CCZ-12 provide a higher surface area compared to CCZ-4. The arrangement of nanocube layers promotes electrochemical reactions and contributes to improving the stability and performance of the nanostructure.

[0142] As such, the FESEM image in FIG. 8 clearly shows that the CCZ-4 and CCZ-12 materials each have a nanosphere shape with a hollow internal structure, and a multilayer structure of nanoparticle layers and nanocube layers. This is in complete agreement with the nanostructure design described in the claims and demonstrates that the technical implementation of the present invention can provide structural stability and electrochemical performance simultaneously.

[0143] Figure 9 is a diagram comparing the electrochemical characteristics of CCZ-4 / NF, CCZ-8 / NF, and CCZ-12 / NF electrodes.

[0144] First, Figure 910 compares the cyclic voltammetry (CV) curves of the CCZ-4 / NF, CCZ-8 / NF, and CCZ-12 / NF electrodes. All electrodes were analyzed in a potential window of 0-0.55 V at a scan rate of 15 mV / s.

[0145] As a result, the CCZ-8 / NF electrode exhibited the largest oxidation and reduction peak regions, indicating that the unique nanostructural design of the core and shell layers of CCZ-8 / NF optimized electron-ion interactions. In contrast, the CCZ-4 / NF electrode showed low electrochemical activity due to its single-layer, incomplete nanospheres, while the CCZ-12 / NF electrode displayed somewhat lower performance as internal pore accessibility was reduced due to excessive growth.

[0146] Figure 920 compares the galvanic charge / discharge (GCD) profiles of the three electrodes. This experiment was performed at a current density of 3 mA / cm². Consequently, the CCZ-8 / NF electrode exhibited the longest discharge time, suggesting that it was able to store more charge due to its hollow core and multilayer shell structure. The CCZ-4 / NF electrode showed the shortest discharge time due to its incomplete layered structure, while the CCZ-12 / NF electrode showed degraded performance as charge / ion diffusion was restricted due to excessive growth.

[0147] Figure 930 of Fig. 9 shows a graph comparing the areal capacitance values ​​of the three electrodes. As a result, the CCZ-8 / NF electrode exhibited the best performance, recording an areal capacitance of 51.5 μAh / cm². In contrast, the CCZ-4 / NF electrode showed a relatively low capacitance of 20.1 μAh / cm², and the CCZ-12 / NF electrode showed a relatively low capacitance of 44.8 μAh / cm². This is attributed to the hollow core-shell structure of the CCZ-8 / NF, which increased the interaction area between the electrode and the electrolyte and optimized the charge transfer path.

[0148] These results of the present invention clearly demonstrate that the CCZ-8 / NF electrode possesses excellent electrochemical properties and shows potential as an electrode material suitable for energy storage systems.

[0149] FIG. 10 is a diagram disclosing the CV, GCD curves, and area capacitance characteristics of the CCZ-4 / NF electrode.

[0150] FIG. 10 is a detailed comparison and evaluation of the electrochemical characteristics of the CCZ-4 / NF electrode, demonstrating the performance of the electrode material of the present invention through cyclic voltammetry (CV) curves, galvanic charge / discharge (GCD) curves, and area capacitance analysis.

[0151] Figure (1010) shows the cyclic voltammetry (CV) curve of the CCZ-4 / NF electrode. CV measurements were performed at various scan rates from 5 mV / s to 30 mV / s. At each scan rate, the CCZ-4 / NF electrode exhibits distinct oxidation and reduction peaks, which demonstrates the excellent electrochemical activity of the electrode. As the scan rate increases, the area under the CV curve gradually increases, indicating the excellent reversibility of the electrode. The CV curve suggests the effective progression of redox reactions at the electrochemically active sites, which is directly related to the structural characteristics of the electrode material described in the claims.

[0152] Figure (1020) shows the Galvanostatic Charge-Discharge (GCD) curve of the CCZ-4 / NF electrode. These GCD measurements were performed at various current densities ranging from 1 mA / cm² to 10 mA / cm². At low current densities, the discharge time is maintained for a relatively long period, which indicates the high electrochemical capacity of the electrode. The discharge curve of the CCZ-4 / NF electrode is linear, indicating that charge transfer within the electrode is uniform. Even at high current densities, the GCD curve maintains a stable shape, demonstrating the excellent durability and ability to maintain performance at high currents of the electrode.

[0153] Figure (1030) shows the results of comparing the areal capacity of the CCZ-4 / NF electrode. The areal capacity was calculated based on GCD data and was measured to be up to about 21.6 μAh / cm² at a current density of 1 mA / cm². This demonstrates that the electrode has excellent electrochemical capacity and is suitable as an energy storage device. As the current density increases, the areal capacity decreases slightly but still maintains a high value (about 14 μAh / cm² at 10 mA / cm²), which shows that the electrode can operate stably under various current conditions.

[0154] FIG. 10 demonstrates that the CCZ-4 / NF electrode exhibits excellent electrochemical performance under various scan rate and current density conditions, highlighting the practical applicability of the hybrid supercapacitor applications of the present invention. These results clearly show that the CCZ-4 / NF electrode satisfies the structural and functional characteristics mentioned in the claims and provides high electrochemical stability and excellent energy storage performance.

[0155] FIG. 10 is a detailed comparison and evaluation of the electrochemical characteristics of the CCZ-4 / NF electrode, demonstrating the performance of the electrode material of the present invention through cyclic voltammetry (CV) curves, galvanic charge / discharge (GCD) curves, and area capacitance analysis.

[0156] FIG. 11 is a diagram disclosing the CV, GCD curves, and area capacitance characteristics of the CCZ-8 / NF electrode.

[0157] FIG. 11 discloses the results of a detailed analysis of the electrochemical characteristics of the CCZ-8 / NF electrode through CV curves, GCD curves, and area capacitance data. Each figure specifically explains the excellent electrochemical performance of the electrode material of the present invention based on the structural and functional characteristics of the CCZ-8 / NF electrode.

[0158] Figure (1110) shows the cyclic voltammetry (CV) curve of the CCZ-8 / NF electrode. CV analysis was performed at various scan rates from 5 mV / s to 30 mV / s. The CCZ-8 / NF electrode exhibits distinct oxidation and reduction peaks at all scan rates, demonstrating that electrochemical redox reactions are effectively taking place at the electrode. As the scan rate increases, the area under the CV curve gradually increases, indicating that the electrode of the present invention has high redox activity and provides fast ion and electron transfer rates. These characteristics are interpreted as a result of the increased active surface area of ​​the electrode due to the hollow structure and multilayer structure design described in the claims.

[0159] Figure (1120) shows the galvanic charge / discharge (GCD) curve of the CCZ-8 / NF electrode. GCD tests were performed at various current densities ranging from 1 mA / cm² to 10 mA / cm². The discharge curve has a non-linear shape, indicating that the electrode of the present invention has an energy storage mechanism based on a Faradic reaction. At low current densities, the discharge time is maintained for a long period, suggesting that the electrode material has a high electrochemical capacity. Even at high current densities, the discharge curve maintains a stable shape, demonstrating the excellent durability and electrochemical stability of the electrode. In particular, the upper part of the discharge curve shows slight curvature, while the lower part forms a linear shape, indicating that it follows a mixed energy storage mechanism.

[0160] Figure (1130) shows the results of comparing the areal capacity data of the CCZ-8 / NF electrode. The areal capacity was calculated based on GCD data, and the CCZ-8 / NF electrode recorded a maximum areal capacity of 53.7 μAh / cm² at a current density of 1 mA / cm². This indicates that the electrode has high electrochemical activity and can provide excellent performance as an energy storage device. Although the areal capacity decreases slightly as the current density increases, it maintains about 47.2 μAh / cm² even at a high current density of 10 mA / cm², which shows that the electrode can provide stable electrochemical performance under various current conditions.

[0161] The results of FIG. 11 demonstrate that the CCZ-8 / NF electrode satisfies the structural characteristics described in the claims, and in particular, that the multilayer structure and hollow core design increase the interaction area between the electrode and the electrolyte, thereby improving electrochemical performance. This supports the fact that the hybrid supercapacitor electrode of the present invention has practical applicability as a material capable of simultaneously providing high energy density and excellent durability.

[0162] FIG. 12 is a diagram disclosing the CV, GCD curves, and area capacitance characteristics of the CCZ-12 / NF electrode.

[0163] Figure 12 (1210) shows the CV curve of the CCZ-12 / NF electrode. This CV curve was analyzed at various scan rates from 5 mV s¹ to 30 mV s¹ and performed within a fixed potential window of 0–0.55 V. The CV curve of the CCZ-12 / NF electrode includes oxidation and reduction peaks, which indicates that the material exhibits electrochemical activity through reversible redox reactions. The area under each CV curve increases proportionally with the scan rate, demonstrating high electrochemical activity and reversibility.

[0164] Figure 12 (1220) shows the GCD curve of the CCZ-12 / NF electrode, which was performed at various current densities from 1 mA cm² to 10 mA cm². This GCD curve shows nonlinear charge and discharge curves, suggesting that the material exhibits Faradic-type redox activity. Although the discharge time decreases as the current density increases, the shape of the discharge curve remains stable, which demonstrates the high electrochemical stability of the CCZ-12 / NF electrode.

[0165] Figure 12 (1230) shows the areal capacitance characteristics of the CCZ-12 / NF electrode. These characteristics were calculated based on the GCD curve and show that the areal capacitance value changes with current density. The CCZ-12 / NF electrode achieves an areal capacitance of up to 47.3 μAh cm² at 1 mA cm², which demonstrates the potential of the electrode material with high electrochemical properties.

[0166] The CCZ-12 / NF electrode of the present invention comprises a multilayer core-shell structure, which provides a high surface area and numerous electrochemically active sites, thereby exhibiting high electrochemical properties. The outer layer of the CCZ-12 / NF electrode is composed of nanocubes, which enhances the interaction between the electrode and the electrolyte, thereby improving the efficiency of redox reactions. The CCZ-12 / NF electrode is evaluated as a suitable material for high-performance hybrid supercapacitor applications.

[0167] FIG. 13 discloses the results of a detailed analysis of the electrochemical characteristics of an activated carbon-coated nickel foam (AC / NF) electrode through cyclic voltammetry (CV) curves, galvanostatic charge-discharge (GCD) curves, and area capacitance data. Each figure demonstrates the influence of the structural and functional characteristics of the AC / NF electrode on electrochemical performance and highlights the technical validity of the present invention.

[0168] Figure 1310 shows the CV curves of the AC / NF electrode. CV analysis was performed at various scan rates from 5 mV / s to 30 mV / s and measured within a potential window of -0.9 V to 0.0 V. The AC / NF electrode exhibits distinct oxidation and reduction peaks at all scan rates, indicating that reversible redox reactions are actively taking place at the electrode. The area under each CV curve increases proportionally with increasing scan rate, demonstrating that the electrode exhibits excellent electrochemical activity and reversibility. In particular, high ion exchange and charge transfer efficiency are observed at the electrode surface. This is directly linked to the structural design related to the increased active surface area described in the claims.

[0169] Figure 1320 shows the GCD curve of the AC / NF electrode. GCD tests were performed at various current densities ranging from 1.5 mA / cm² to 10 mA / cm². The discharge curve exhibits clear linearity, which demonstrates that the electrode material operates stably in electrochemical reactions. At low current densities (1.5 mA / cm²), the discharge time is maintained for a long period, which shows that the electrode can provide high electrochemical capacity. Even at high current densities (10 mA / cm²), the discharge curve maintains a stable shape, which demonstrates the excellent durability and electrochemical stability of the AC / NF electrode.

[0170] Figure 1330 shows the areal capacity of the AC / NF electrode calculated at various current densities. The areal capacity was calculated based on GCD data and recorded a maximum areal capacity of approximately 320 μF / cm² at a current density of 1.5 mA / cm². Although the areal capacity gradually decreases as the current density increases, it maintains approximately 250 μF / cm² even at a high current density of 10 mA / cm², demonstrating that the electrode can provide stable performance even under high current conditions. This is a result of the activated carbon coating structure mentioned in the claims increasing the interaction area between the electrode and the electrolyte and maximizing electrochemical reactivity.

[0171] The analysis results of Fig. 13 demonstrate that the AC / NF electrode satisfies the structural characteristics described in the claims, and in particular, that the combination of the activated carbon coating structure and the nickel foam substrate significantly improves the electrochemical properties of the electrode. The AC / NF electrode provides high redox activity, a stable discharge curve, and excellent areal capacity, clearly demonstrating its potential as a cathode material suitable for hybrid supercapacitor applications. This supports the technical excellence of the present invention and demonstrates the practical applicability of the AC / NF electrode in various energy storage applications.

[0172] FIG. 14 is a drawing illustrating a method for manufacturing a three-dimensional nanostructure according to one embodiment.

[0173] The method for manufacturing a three-dimensional nanostructure according to the present invention comprises the step of forming a hollow structure multilayer nanosphere comprising a mixed metal oxide including cobalt, copper, and zinc and a nickel-based outer layer.

[0174] First, cobalt acetate, copper acetate, and zinc acetate are mixed in an ethylene glycol solvent to form a homogeneous mixture (1401). Ethylene glycol acts as a solvent and a reducing agent, ensuring uniform dispersion of metal ions. This mixture undergoes sonication and vigorous stirring, during which polyvinylpyrrolidone (PVP) acts as a structural indicator. PVP binds with cobalt, copper, and zinc ions to form stable complexes and prevents the aggregation of metal ions. This step maintains the mixture homogeneously, allowing it to react evenly in subsequent reactions.

[0175] The formed mixture is converted into a hollow-core single-shell structure nanosphere through a solvothermal reaction (1402).

[0176] This solvothermal reaction is carried out in an ethylene glycol solvent at a temperature of 160°C for 8 hours under pressurized conditions. During the reaction, cobalt, copper, and zinc ions are reduced, and a mixed metal oxide layer is formed. The internal structure is designed as a hollow core with an internal diameter of approximately 500–1000 nm. The hollow structure is a critical design element for maximizing electrochemically active sites, and the inner core contains a layer of nanoparticles composed of metal oxides. The outer shell consists of a single layer and maintains a uniform and stable structure.

[0177] A hollow core single-shell nanosphere is immersed in a nickel nitrate solution to form a double-shell structure (1403). At this stage, a chemical vapor deposition process is performed at a temperature of about 80°C. The nickel coating forms nickel nanosheets on the surface of the nanosphere, and the outer layer consists of a porous structure with a thickness of about 10 to 50 nm. The double-shell structure provides structural stability through chemical interactions between the inner core and the outer shell, and increases the density of electrochemically active sites. The nanosheet structure of the outer layer optimizes ion exchange between the electrode and the electrolyte and improves energy storage efficiency.

[0178] The formed nanospheres are washed with DIW and ethanol and then dried at 70°C. The washing process is an essential step to obtain pure nanostructures by removing impurities and reaction residues (1404). The dried nanospheres are composed of a multilayer core-shell structure, with the inner core consisting of a nanoparticle layer, the middle layer consisting of a nanocube layer, and the outer layer consisting of a nanosheet layer. Each layer provides electrochemically active sites and maximizes the interaction area between the electrode and the electrolyte. The finally formed three-dimensional nanostructure has a porosity of approximately 30–70% and provides high electrochemical performance.

[0179] The three-dimensional nanostructure formed by the manufacturing method of the present invention is based on a hollow core and a multilayer shell structure. This nanostructure possesses electrochemical stability and high charge storage capacity, and is suitable for various energy storage and conversion devices, such as hybrid supercapacitors, lithium-ion batteries, and catalytic applications. The manufacturing process presents an efficient method capable of providing high-performance electrode materials despite being simple, thereby supporting the technical excellence of the present invention.

[0181] Although the embodiments have been described above with reference to the limited drawings, those skilled in the art can make various modifications and variations from the description above. For example, suitable results can be achieved even if the described techniques are performed in a different order than described, and / or the components of the described system, structure, device, circuit, etc. are combined or assembled in a form different from described, or replaced or substituted by other components or equivalents.

[0182] Therefore, other implementations, other embodiments, and equivalents to the claims also fall within the scope of the claims set forth below.

Claims

Claim 1 A three-dimensional nanostructure characterized in that the interior has a hollow structure, wherein the hollow structure comprises: an inner layer formed of a nanoparticle layer composed of cobalt, copper, and zinc; an intermediate layer composed of nanocubes formed on the inner layer; and an outer layer composed of nanosheets formed on the intermediate layer. Claim 2 A three-dimensional nanostructure according to claim 1, characterized in that the outer layer is finished with a nickel coating having a thickness within the range of 10 to 50 nm. Claim 3 A three-dimensional nanostructure according to claim 1, characterized in that the cobalt, copper, and zinc constituting the nanoparticle layer have an average particle size within the range of 10 to 50 nm. Claim 4 A three-dimensional nanostructure according to claim 1, wherein the nanocube is characterized by having an average side length within the range of 50 to 200 nm. Claim 5 A three-dimensional nanostructure according to claim 1, characterized in that the nanosheet has a thickness within the range of 5 to 20 nm. Claim 6 A three-dimensional nanostructure according to paragraph 2, characterized in that the nickel coating is formed through a chemical vapor deposition process. Claim 7 A three-dimensional nanostructure according to claim 1, characterized in that the hollow structure has an average diameter of the internal space within the range of 500 to 1000 nm. Claim 8 A three-dimensional nanostructure according to claim 1, characterized in that the nanostructure is formed using polyvinylpyrrolidone (PVP) as a structural indicator. Claim 9 A three-dimensional nanostructure according to claim 1, characterized in that the hollow structure is formed through a solvothermal synthesis process using ethylene glycol as a solvent. Claim 10 A three-dimensional nanostructure according to claim 1, characterized in that the nanoparticle layer is composed of a mixed metal oxide of cobalt, copper, and zinc. Claim 11 A three-dimensional nanostructure according to claim 1, characterized in that the intermediate layer is composed of cobalt and copper oxides arranged in a nanocube structure. Claim 12 A three-dimensional nanostructure according to claim 1, characterized in that the nanosheet is composed of nickel oxide or a nickel-cobalt alloy. Claim 13 A three-dimensional nanostructure according to claim 2, characterized in that the nickel coating is formed by immersing the hollow structure in a nickel nitrate solution and heating it. Claim 14 A three-dimensional nanostructure according to claim 1, characterized in that the nanostructure is assembled to have a multilayer structure after drying treatment. Claim 15 A three-dimensional nanostructure characterized by being designed to have a multilayer core-shell structure in claim 1. Claim 16 A three-dimensional nanostructure according to claim 1, characterized in that the hollow structure has a porosity within the range of 30 to 70% to increase the density of electrochemically active sites. Claim 17 A method for manufacturing a three-dimensional nanostructure having a hollow core and a multilayer structure, comprising the steps of: mixing cobalt acetate, copper acetate, and zinc acetate in an ethylene glycol solvent to form a uniform mixture through sonication and stirring; converting the formed mixture into a nanosphere having a hollow core single-shell structure through a solvothermal reaction; immersing the converted nanosphere having a hollow core single-shell structure in a solution containing nickel nitrate to form a double shell including a nanosheet structure; and washing and drying the formed double shell to manufacture a three-dimensional nanostructure having a multilayer structure. Claim 18 A method for manufacturing a three-dimensional nanostructure according to claim 17, characterized by including the step of adding polyvinylpyrrolidone (PVP) as a structural indicator used to form the mixture.

Citation Information

Patent Citations

  • All Solid secondary battery

    KR1020240078475A

  • Hierarchical electrode for high-performance hybrid supercapacitor, manufacturing method thereof, and supercapacitor including the same

    KR1020240082656A

  • Electrocatalyst, Cathode and Electrochemical system comprising electrocatalyst, and Preparation method thereof

    KR1020250090936A

  • Composite material, super-capacitor comprising thereof, and preparing method of composite material

    KR102720836B1